Minimally Invasive Percutaneous Plate Osteosynthesis (MIPPO) Combined with Onionskin-Like Autologous Bone Grafting: A New Technique for Treatment of Tibial Nonunion - Wu, Dankai; Mao, Fengmin; Yuan, Baoming; Ren, Guangkai; Liu, He; Peng, Chuangang (Medical science monitor, 2019)
BACKGROUND Established tibial nonunions rarely heal without secondary intervention; revision surgery is the most common intervention. Herein, we evaluated the clinical outcomes of patients with tibial nonunion treated with a new technique - minimally invasive percutaneous plate osteosynthesis (MIPPO) - combined with a new onionskin-like autologous bone grafting method. MATERIAL AND METHODS From 2010 to 2013, 18 patients with tibial nonunions (average bone defect: 9.5 mm) were treated with MIPPO technology combined with onionskin-like autologous bone grafting. Indices for clinical evaluation included operative time, ﬂuoroscopy time, blood loss, hospital stay, healing time, postoperative complaints, radiographic performances, the Short Musculoskeletal Function Assessment (SMFA) questionnaire, and the American Orthopedic Foot & Ankle Society (AOFAS) ankle-hindfoot score. RESULTS The average operation and ﬂuoroscopy times for tibial nonunion were 65 min and 15.5 s, respectively, with a total blood loss of 107.7 mL. The mean duration of hospital stay was 12.8 days. The mean follow-up time was 11.9 months, and all patients achieved radiologically confirmed bony healing in an average time of 13.1 weeks. No lower-leg deformity, fixation failure, infection, and vascular, or nerve injuries were recorded in any patient, and only 4 patients complained of slight limb pain upon total weight-bearing at the end of follow-up. The SMFA and AOFAS ankle-hindfoot scores of patients were graded excellent in 14 (77.8%) and good in 4 (22.2%), indicating high functional recovery. CONCLUSIONS MIPPO technology combined with onionskin bone grafting is an efficient method to treat patients with tibial nonunion, especially for patients with poor soft tissue condition.